2017
DOI: 10.1111/ceo.13116
|View full text |Cite|
|
Sign up to set email alerts
|

Flow dynamics of cerebrospinal fluid between the intracranial cavity and the subarachnoid space of the optic nerve measured with a diffusion magnetic resonance imaging sequence in patients with normal tension glaucoma

Abstract: Diffusion-weighted imaging provides a method to evaluate CSF flow within the subarachnoid space of the optic nerve in a non-invasive manner. Compared to healthy controls, patients with normal tension glaucoma measure a significantly lower flow-range ratio. This finding suggests a possible role of impaired CSF dynamics in the pathophysiology in normal tension glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 25 publications
1
32
0
2
Order By: Relevance
“…Studies applying computer assisted cisternography in patients with normal tension glaucoma and papilledema demonstrated impaired cerebrospinal fluid dynamics in the subarachnoid space of the optic nerve, a condition that is now described as optic nerve compartment syndrome (ONCS) [2326]. Using our established model we demonstrated that pathophysiological flow conditions, as observed during ONCS, altered the trancriptomic profile of phMECs.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Studies applying computer assisted cisternography in patients with normal tension glaucoma and papilledema demonstrated impaired cerebrospinal fluid dynamics in the subarachnoid space of the optic nerve, a condition that is now described as optic nerve compartment syndrome (ONCS) [2326]. Using our established model we demonstrated that pathophysiological flow conditions, as observed during ONCS, altered the trancriptomic profile of phMECs.…”
Section: Discussionmentioning
confidence: 88%
“…Applying our model, we evaluated the response of MECs to conditions of pathophysiological flow dynamics as observed in ONCS and analyzed their transcriptional profile using RNA sequencing. Although there are studies of our and other groups that employ diffusion MRI to measure CSF fluid dynamics within the brain, spinal canal and optic nerve SAS [30, 31], it is at the current time not feasible to obtain absolute CSF flow rates due to technical limitations. However it is possible to measure a so called flow-range ratio that allows the relative measurement of CSF flow rate by diffusion MRI imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Further, studies using computer-assisted cisternography demonstrated reduced contrast density in the orbital portion of patients with elevated ICP [8], as well as in patients with NTG [6]. In addition, reduced CSF velocity in the subarachnoid space of optic nerves in patients with NTG was confirmed with a Stejskal-Tanner monopolar diffusion sequence on MRI, a new noninvasive method for the study of CSF dynamics [11]. As local pressure measurements in the subarachnoid space of the optic nerve are not possible in a clinical setting, the diameter of the optic nerve sheath can serve as an indicator of pressure.…”
mentioning
confidence: 85%
“…Recent research onto the pathogenesis of glaucoma focused on the composition and role of CSF. In a cohort of NTG patients, we demonstrated by using computer assisted tomography and MRI assisted flow studies that there were impaired CSF dynamics within the subarachnoid space of the optic nerve [ 9 , 10 ]. CSF turnover impairment was most pronounced in the optic nerve portion behind the globe, the so-called bulbar region of the optic nerve [ 11 ].…”
Section: Other Mechanisms Than High Iop Involved In the Pathophysiolomentioning
confidence: 99%